Structural and functional analysis of the inhibition of equine glutathione transferase A3-3 by organotin endocrine disrupting pollutants. (1st January 2021) - Škerlová, Jana; Ismail, Aram; Lindström, Helena; Sjödin, Birgitta; Mannervik, Bengt; Stenmark, Pål
Abstract: Organotin compounds are highly toxic environmental pollutants with neurotoxic and endocrine-disrupting effects. They are potent inhibitors of glutathione transferases (GSTs), thus impeding their detoxication and antioxidant functions. Several GSTs, including equine GST A3-3 (EcaGST A3-3), exhibit steroid double-bond isomerase activity and are involved in the biosynthesis of testosterone and progesterone. We have performed enzyme kinetics analyses of the inhibition of EcaGST A3-3 by organotin compounds. We have also solved crystal structures of EcaGST A3-3 in complexes with glutathione, and with glutathione together with covalently bound triethyltin. Our structural data indicate that the tin atom forms strong bonds with a covalent character not only with the glutathione, but also with a tyrosyl residue of the enzyme itself, thereby preventing the release of the glutathione-organotin adduct and completely blocking the enzyme function. This work presents a structural basis for the general mechanism of GST inhibition by organotin compounds and contributes to the understanding of their neurotoxic and endocrine disrupting effects. Graphical abstract: Image 1 Highlights: Organotin pollutants inhibit glutathione transferases catalyzing hormone synthesis. Triethyltin binds covalently to glutathione and to a key residue in the active site. The binding explains the endocrine disrupting and neurotoxic effects of organotins. Abstract : Our enzyme kinetics and structural data on EcaGST A3-3 explain on a molecular level the neurotoxic and endocrine disrupting effects of organotin pollutants.